The Cellular and Developmental Roles of Cullins, Neddylation, and the COP9 Signalosome in Dictyostelium discoideum - Kim, William D.; Mathavarajah, Sabateeshan; Huber, Robert J. (Frontiers in Physiology, 2022)
Cullins are core components of cullin-RING E3 ubiquitin ligases (CRLs), which regulate the degradation, function, and subcellular trafficking of proteins. Cullins are post-translationally regulated through neddylation, a process that conjugates the ubiquitin-like modifier protein neural precursor cell expressed developmentally downregulated protein 8 (NEDD8) to target cullins, as well as non-cullin proteins. Counteracting neddylation is the deneddylase, COP9 signalosome (CSN), which removes NEDD8 from target proteins. Recent comparative genomics studies revealed that CRLs and the CSN are highly conserved in Amoebozoa. A well-studied representative of Amoebozoa, the social amoeba Dictyostelium discoideum, has been used for close to 100 years as a model organism for studying conserved cellular and developmental processes due its unique life cycle comprised of unicellular and multicellular phases. The organism is also recognized as an exceptional model system for studying cellular processes impacted by human diseases, including but not limited to, cancer and neurodegeneration. Recent work shows that the neddylation inhibitor, MLN4924 (Pevonedistat), inhibits growth and multicellular development in D. discoideum, which supports previous work that revealed the cullin interactome in D. discoideum and the roles of cullin proteins and the CSN in regulating cellular and developmental processes during the D. discoideum life cycle. Here, we review the roles of cullins, neddylation and the CSN in D. discoideum to guide future work on using this biomedical model system to further explore the evolutionarily conserved functions of cullins and neddylation.